E-Commerce in German Agriculture: A Case Study Investigating Farmer Satisfaction Applying the Thinking Aloud Method - Dorothee Schulze Schwering; Lena Focke-Meermann; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2023)
E-commerce in agriculture is gaining increasing attention, but market penetration is currently low, and companies are barely exploiting its full potential. Identifying and satisfying farmers' expectations of e-commerce websites for farm inputs is crucial to reduce this opportunity loss. This paper presents a qualitative case study using the "thinking aloud" method, investigating the factors of an agricultural e-commerce site that need to be improved to increase customer satisfaction. The results reveal that farmers' dissatisfaction with and reluctance to engage in agricultural e-commerce are linked to deficiencies in the store design. These deficiencies are especially apparent in the incongruent design of off- and online stores. Congruity is needed not only in terms of price but, more importantly, in terms of design (e.g., navigation, product order) and services. However, this is often lacking. High channel congruence improves trust in the online provider and keeps perceived transaction costs low. The study emphasizes the importance of customer centricity and a channel integration strategy in agricultural trade and provides indications of which elements lead to higher customer satisfaction.
Keywords: 330